Wheat Grain Yield and Grain Protein Concentration Response to Nitrogen Rate During the 2018–2019 Growing Season in Kansas - Romulo P. Lollato; Kavan E. Mark; Brent R. Jaenisch (Kansas Agricultural Experiment Station Research Reports, 2020)
The objective of this project was to evaluate winter wheat grain yield and grain protein concentration responses to nitrogen (N) rate in the state of Kansas during the 2018–2019 growing season. Experiments evaluating the response of the wheat variety Zenda to four nitrogen rates (0, 50, 100, and 150 lb N/a) were established at four locations. In-season measurements included flag leaf N concentration, grain yield, yield components, and grain protein concentration. Flag leaf N concentration ranged from 2.4 to 4.1% across all environments and treatments, and increases in N rates increased flag leaf N concentration linearly. Grain yield ranged from 36.3 to 94.4 bu/a and increased with increases in N rate usually following quadratic relationships at all locations except for Belleville, where no response was observed, likely due to the high organic matter levels. Grain protein concentration ranged from 11 to 15% across all locations and treatments and increases in N rates increased grain protein concentration following a usually linear relationship; however, the quadratic yield response to N rate, coupled to the linear protein response to N rate, indicated that greater N rates might be needed to maximize protein as compared to maximizing yields. Both relative grain yield and relative grain protein concentration variables calculated relative to the maximum in each respective environment, were related to flag leaf N concentration in a linear-plateau way, suggesting that flag leaf N concentration could be used as a diagnostic tool for crop N status.
Keywords: wheat; nitrogen rate; nitrogen concentration; flag leaf